Total bilirubin-to-albumin ratio and short- and long-term all-cause mortality in acute pancreatitis: Evidence from the MIMIC-IV database - XingYi Yang; Min Zhang; LiHong Lv; Xuyong Chen; ZhenMei Li (PLoS ONE, 2025)
Background The Total Bilirubin-to-Albumin Ratio (TBAR) is widely recognized and applied as a biomarker in the prognostic evaluation of various diseases. However, its role in predicting survival outcomes in patients with acute pancreatitis (AP) remains underexplored. This study aims to investigate the association between TBAR levels and mortality rates in AP patients, thereby providing a novel prognostic indicator for clinical use. Methods This study investigates the association between TBAR and mortality in AP patients. We stratified patient data using X-tile software to analyze intergroup differences. Risk factors significantly associated with mortality were identified through univariate and multivariate regression analyses. Kaplan-Meier (KM) analysis evaluated TBAR’s impact on survival, while Receiver Operating Characteristic (ROC) analysis assessed its predictive accuracy, sensitivity, and Area Under the Curve (AUC) for mortality. To ensure robustness, we used Restricted Cubic Spline (RCS) modeling to explore non-linear relationships and performed subgroup analyses to verify the consistency of the TBAR mortality association across patient subgroups. Result This study included 477 patients. Using X-tile software, we set the optimal TBAR cutoff at 1.33 based on 28-day mortality. Patients were categorized into high-risk (TBAR ≥ 1.33) and low-risk (TBAR < 1.33) groups. Elevated TBAR significantly correlated with increased mortality at multiple time points (7, 14, 21, 28, 90, and 365 days; P < 0.05). KM analysis confirmed lower survival rates in the high-risk group at all time points (P < 0.05). ROC analysis showed TBAR’s predictive accuracy for mortality was comparable to the SOFA score and superior to other indicators. RCS modeling revealed a linear TBAR mortality relationship. Subgroup analyses showed no significant interactions between TBAR and most subgroups. Conclusion The TBAR is strongly correlated with short-term and long-term mortality in patients with acute pancreatitis.